Available for plants phosphorus in the floodplain catenas of the Amur River - A. V. Martynov (Бюллетень Почвенного института им. В.В. Докучаева)
This work was carried out to study the content and distribution of available for plants phosphorus in different types of floodplain soils along five catenas located in the upper and the middle Amur. It was found that the available for plants phosphorus forms in the soils of floodplains are influenced by the following factors: the structure of the river system, the type of floodplain, the type of vegetation cover, and soil-forming processes. During the long-term transportation of alluvium along the river bed, its hydrogenic weathering occurs with the release of phosphorus into river waters. In the absence of tributaries serving as additional sources of alluvium, the phosphorus content decreases downstream. More intense floodplain and alluvial processes in small floodplains provide renewal of the soil profile and replenishment of phosphorus reserves. In the soils under the birch forest, there is a significant accumulation of phosphorus, in comparison with the soils under meadow vegetation. The development of gley processes leads to active mobilization of phosphorus, but the long-term exposure leads to the depletion of its total reserves. The illimerization processes, initiated and developing when the floodplain hydrological regime of alluvial soils is changed to another one, promote the migration of iron oxides and phosphorus, adsorbed by the former, beyond the soil profile. To summarize, the average content of available for plants phosphorus, depending on the type of soil, decreases downstream from 300–100 mg/kg in the upper Amur to 170–20 mg/kg in the middle Amur. Available for plants of phosphorus are best provided in primitive alluvial layered soils, while in residual floodplain brunezems the lowest content is recorded.